Incidental finding and conservative management of left main coronary atresia in an adult patient: a case report. Issue 2 (22nd February 2021) - Talanas, Giuseppe; Corda, Giulia; Parodi, Guido; Portoghese, Michele
Abstract: Background: Left main (LM) coronary atresia (LMCA) is a rare coronary anomaly where the LM is congenitally absent and a variable clinical spectrum can follow. The diagnosis of LMCA is generally made in youth because of the development of symptoms, but very rarely in adulthood. In symptomatic patients, surgical revascularization is recommended, whereas, in asymptomatic patients with LMCA and without inducible myocardial ischaemia, preventive surgical treatment is controversial. Case summary: A 58-year-old male patient with aortic ectasia detected during an echocardiogram performed to evaluate a hypertension-related preclinical cardiac damage and, due to this finding, an echocardiographic follow-up was suggested. Three years later, he was admitted to undergo coronary angiography (CA) after the computed tomography finding of a suspected occlusion of the LM with collateral circulation from right coronary artery (RCA) to left anterior descending and circumflex arteries. CA confirmed an LMCA and the RCA provided blood supply to the left coronary artery through collaterals whose calibre was similar to that of the target left-sided vessels. No obstructive coronary artery disease was detected. In order to detect potential myocardial ischaemia, a technetium-tetrofosmin cardiac single-photon emission computed tomography during maximal exercise-stress test was performed and it did not show a perfusion defect. Medical management with scheduled follow-up visits was deemed to be the best therapeutic option. Discussion: LMCA is a rare anomaly where LM is absent and the RCA provides collateral circulation for left coronary artery. In asymptomatic patients, preventive surgical treatment is controversial.